Du Feu à l'Eau: Source and Flux of Dissolved Black Carbon From the Congo River. Issue 8 (14th August 2020) - Drake, Travis W.; Wagner, Sasha; Stubbins, Aron; Wabakanghanzi, José N.; Dinga, Jean Bienvenu; Six, Johan; Spencer, Robert G. M.
Abstract: Pyrogenic organic residues from wildfires and anthropogenic combustion are ubiquitous in the environment and susceptible to leaching from soils into rivers, where they are known as dissolved black carbon (DBC). Here we quantified and isotopically characterized DBC from the second largest river on Earth, the Congo, using 12 samples collected across three annual hydrographs from 2010 to 2012. We find that the Congo River exports an average of 803 ± 84 Gg‐C as DBC per year, comprising 7.5% of the river's average annual dissolved organic carbon (DOC) flux (10.7 ± 1.2 Tg‐C yr −1 ). Concentrations of DBC were strongly correlated with discharge and DOC concentration, indicating transport limitation for DBC flux from the Congo River Basin. Stable carbon isotopic signatures of DBC revealed a seasonal shift in pyrogenic source from forest dominant to an increasing contribution from savannah biomass, which derives from the North‐South bimodal hydrologic regime within the basin. Our results also indicate that black carbon produced within the Congo Basin is exported by the river on relatively short time scales and that total DBC export will increase with climate change predictions for the central African region. Key Points: The Congo River exports ~803 Gg‐C as dissolved black carbon to the ocean per year, roughly 50% more than particulate black carbon Dissolved black carbon was strongly correlated with discharge and dissolved organic carbon, indicating coinciding transport limitation Stable carbon isotopes of dissolved black carbon showed a seasonal shift in pyrogenic material derived from forest and savannah biomass